Phenolic moulding plastic for key component of optical fiber fusion splicer and preparation method of phenolic moulding plastic

By using alkali catalyzed nitrogen-containing phenolic resin and a large number of inorganic fibers and fillers, combined with silicon powder and glass microbeads, the problem of unstable thermal expansion coefficient and shrinkage of the stage material of the fiber splicer is solved, and phenolic molding materials for key components of the fiber splicer with high temperature resistance and dimensional stability is achieved.

CN119899487APending Publication Date: 2025-04-29ZHEJIANG GOODMIN NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510398913.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing optical fiber splicing machine stage materials have problems such as inconsistent thermal expansion coefficient, unstable shrinkage rate, and difficult to guarantee shape and position tolerance, resulting in poor equipment assembly, poor part interchangeability, and difficult to guarantee accuracy.

Method used

The alkali-catalyzed nitrogen-containing phenolic resin is used as the matrix, and the high temperature resistance and dimensional stability of the material are improved by adding a large number of inorganic fibers and inorganic fillers. At the same time, silicon micropowder and glass microbeads are used to reduce the difference in thermal expansion coefficient and shrinkage.

Benefits of technology

The phenolic molding coefficient of the key components of the fiber splicer has been achieved with relatively consistent thermal expansion coefficient, low shrinkage rate and high temperature resistance (HDT ≥300℃), which meets the moldability and operability requirements of the fiber splicer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of functional phenolic resin molding compounds, in particular to a phenolic resin molding compound for key components of an optical fiber fusion splicer and a preparation method of the phenolic resin molding compound. The phenolic moulding compound is prepared from base-catalyzed nitrogen-containing phenolic resin, silica powder, inorganic fibers, glass beads, a curing accelerator, a release agent, a coupling agent, a plasticizer and a coloring agent. The phenolic moulding compound is prepared from a base-catalyzed nitrogen-containing phenolic resin, silica powder, inorganic fibers, glass beads, a curing accelerator, a release agent, a coupling agent, a plasticizer and a coloring agent. The base-catalyzed nitrogen-containing phenolic resin can be self-crosslinked at a high temperature to form a compact three-dimensional network structure, so that the problems of unstable shrinkage rate and poor high temperature resistance of the traditional phenolic resin are solved; the total mass of the silica powder, the inorganic fibers and the glass beads is 75-83 parts. Compared with the prior art, the phenolic moulding plastic provided by the invention has the advantages of good heat resistance, low expansion coefficient, bending strength, good fluidity and low molding shrinkage rate, and meets good formability and operability in the injection molding process of key components of the optical fiber fusion splicer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional phenolic resin molding materials, and in particular to a phenolic molding material for key components of an optical fiber fusion splicer and a preparation method thereof. Background Art

[0002] Since 1960, when American scientist Maiman invented the world's first laser, it has provided a good light source for optical communications. In the following two decades, people have tackled the problem of optical transmission media and finally made low-loss optical fibers, thus laying the foundation for optical communications. Since then, optical communications have entered a stage of rapid development. As a mainstream method of broadband access, optical fiber has the advantages of large communication capacity, long relay distance, good confidentiality, strong adaptability, small size and light weight, wide source of raw materials and low price. It is expected to be widely used in broadband Internet access, cable TV networking, big data transmission, unmanned driving, etc.

[0003] In practical applications, the connection between optical fibers is generally carried out by hot fusion and cold fusion. The hot fusion method uses the high-voltage arc of the optical fiber fusion splicer to melt two optical fibers and connect them. This method was generally used for long-distance communication construction in the early days. However, with the increase in the national demand for network speed and the rise of fiber-to-the-home, the hot fusion method is also used for short-distance fiber optic laying construction (such as community broadband network and fiber-to-the-home, etc.), and has become the mainstream fiber optic construction method in the world. The optical fiber fusion splicer is the most commonly used equipment in optical fiber laying construction. It is small in size, light in weight, high in precision, and requires portability and reliability. The core alignment optical fiber fusion splicer is equipped with a precise six-motor core alignment mechanism, a specially designed optical lens and software algorithm. It can accurately identify the type of optical fiber and automatically select the matching fusion mode to ensure the fusion quality. It has a high technical content. The optical fiber carrier, as the core component of the fusion splicer, has a complex shape and high dimensional tolerance and position tolerance requirements. At present, the optical fiber fusion splicer carrier generally uses engineering plastics such as PEEK, LCP, PPS or thermosetting phenolic molding compound (PMC). No matter what material is chosen, there are problems of one kind or another, such as inconsistent expansion coefficients, inconsistent shrinkage rates of parts in all directions, and difficulty in ensuring geometric tolerances, resulting in poor equipment assembly, poor parts interchangeability, and difficulty in ensuring accuracy. Summary of the invention

[0004] In order to solve the technical difficulties existing in the above-mentioned prior art, the present application provides a phenolic molding compound product for key components of an optical fiber fusion splicer having relatively consistent and low thermal expansion coefficients in all directions (X, Y, Z), relatively consistent and stable shrinkage rates in all directions (X, Y, Z), and a higher temperature resistance level (HDT≥300°C) and a preparation method thereof.

[0005] In the first aspect, the present application provides a phenolic molding compound for key components of an optical fiber fusion splicer, which is realized by the following technical solutions: A phenolic molding compound for key components of an optical fiber fusion splicer is prepared from the following raw materials in parts by weight: 14 to 16 parts of a base-catalyzed nitrogen-containing phenolic resin, 25 to 35 parts of silicon micropowder, 20 to 25 parts of inorganic fibers, 25 to 35 parts of glass microbeads, 0.5 to 2 parts of a curing accelerator, 0.5 to 2 parts of a release agent, 0.5 to 2.5 parts of a coupling agent, 0.5 to 1.5 parts of a plasticizer, and 0.5 to 1.5 parts of a colorant; The average particle size of the silicon powder is 100 to 200 nm; The inorganic fiber is at least one of alkali-free glass fiber, basalt fiber, and inorganic whisker; The curing accelerator is calcium hydroxide and / or magnesium hydroxide; The release agent is at least one of carnauba wax, polyethylene wax, stearic acid, and stearate; The coupling agent is at least one of mercaptosilane, epoxysilane and aminosilane; The plasticizer is at least one of methanol, ethanol and polyethylene glycol; The colorant is at least one of carbon black, oil-soluble aniline black, iron oxide brown, and iron oxide yellow.

[0006] The phenolic molding compound for key components of the optical fiber fusion splicer in the present invention adopts alkali-catalyzed nitrogen-containing phenolic resin (PF-8104 of Jinan Shengquan), which can self-crosslink at high temperature to form a dense three-dimensional network structure, thereby solving the problems of unstable shrinkage and poor high temperature resistance of traditional phenolic resin. At the same time, a large number of inorganic fillers with different particle sizes are used to improve the dimensional stability and high temperature resistance of the material.

[0007] The invention has the advantages of a phenolic molding compound with a base-catalyzed nitrogen-containing phenolic resin matrix, wherein the phenolic resin is used to ensure the crosslinking density and heat resistance of the matrix material, a large amount of inorganic fibers and inorganic fillers are used to reduce the proportion of organic matter, thereby improving the heat resistance and dimensional stability of the material, and reducing the thermal expansion coefficient of the material, and combining with silicon micropowder with an average particle size of 150 nm and glass microbeads with an average particle size of 5 μm, the ultrafine amorphous silicon micropowder and glass microbeads can be fully filled into the gap between the resin and various fillers, and the filling density of the injection molded part is improved to achieve the effects of reducing the thermal expansion coefficient of the material, minimizing the difference in shrinkage rates in all directions and improving the heat resistance of the material, while ensuring that the material has good fluidity and filling performance, and can meet the requirements of formability and operability of key components of an optical fiber fusion splicer.

[0008] Preferably, the base-catalyzed nitrogen-containing phenolic resin is PF-8104 from Jinan Shengquan.

[0009] The phenolic molding compound for key components of optical fiber fusion splicers provided in the present invention has the advantages of relatively consistent thermal expansion coefficients in all directions (X, Y, Z), and low shrinkage, and relatively consistent and stable shrinkage in all directions (X, Y, Z), which meets the good formability and operability during the injection molding process of key components of optical fiber fusion splicers. In addition, the phenolic molding compound for key components of optical fiber fusion splicers provided in the present invention has a higher temperature resistance grade, HDT ≥ 300 ° C, which meets the heat-resistant processing requirements during the injection molding process of key components of optical fiber fusion splicers, and has excellent resistance to thermal oxidation degradation.

[0010] Preferably, the inorganic whisker is at least one of aluminum oxide whisker, aluminum nitride whisker, silicon dioxide whisker, silicon nitride whisker, polycrystalline mullite whisker, polycrystalline mullite ceramic whisker, and potassium titanate whisker.

[0011] Preferably, the inorganic fiber is composed of alkali-free glass fiber and inorganic whisker in a mass ratio of (9-19):1.

[0012] Preferably, the inorganic fiber is composed of alkali-free glass fiber, aluminum nitride whisker and silicon nitride whisker; the mass ratio of the alkali-free glass fiber, aluminum nitride whisker and silicon nitride whisker is (40-45):(0.5-2.0):(0.5-1.0).

[0013] Preferably, the glass microspheres are 1800 mesh sieve material with an average particle size of 5±0.2 μm; the particle size distribution curve of the glass microspheres shows D 10 =1.7~1.8μm, D 50 =4.8~5.2μm, D 90 =7.5~7.8μm.

[0014] The inorganic whiskers introduced in the present invention can be fully filled into the gaps between the resin and various fillers, thereby increasing the filling density of the injection molded parts to reduce the thermal expansion coefficient of the material, minimize the difference in shrinkage rates in all directions, and improve the heat resistance of the material. At the same time, the tensile mechanical properties and anti-aging properties of the phenolic molding compound can be effectively improved.

[0015] Preferably, the glass beads are glass beads aggregate, which is composed of the following raw materials in percentage by mass: 5-10% of glass beads discharged from a 1250 mesh sieve, 50-75% of glass beads discharged from a 1800 mesh sieve, 10-30% of glass beads discharged from a 2500 mesh sieve, and the remainder of glass beads discharged from a 5000 mesh sieve.

[0016] Preferably, the glass beads are glass beads aggregate, which is composed of the following raw materials in the following mass percentages: 10% of glass beads discharged from a 1250 mesh sieve, 60% of glass beads discharged from a 1800 mesh sieve, 20% of glass beads discharged from a 2500 mesh sieve, and 10% of glass beads discharged from a 5000 mesh sieve.

[0017] Glass bead aggregates can be more fully filled into the gaps between resin and various fillers, effectively increasing the filling density of injection molded parts, thereby better achieving the effect of reducing the thermal expansion coefficient of the material, minimizing the difference in shrinkage rates in all directions and improving the heat resistance of the material, while also ensuring that the injection molding material still has good fluidity and filling performance. In addition, it can effectively eliminate internal defects of injection molded parts and improve the overall tensile strength and impact toughness.

[0018] Preferably, the silicon micropowder, inorganic fiber and glass microbeads are all surface modified before mixing. The surface modification treatment method is as follows: Step 1: According to the ingredient list of phenolic molding compound for key parts of optical fiber fusion splicer, accurately measured silicon micropowder, inorganic fiber and glass microbeads are mixed evenly to obtain a mixed filler; at the same time, an aminosilane aqueous solution is prepared: 4 to 8 parts of aminosilane are mixed evenly with 992 to 996 parts of deionized water to obtain an aminosilane aqueous solution with a concentration of 0.4-0.8wt%; Step 2: add 5 to 10 parts of the mixed filler to 200 to 250 parts of the aminosilane aqueous solution, stir mechanically at 100 to 200 rpm for 5 to 10 minutes, then perform ultrasonic dispersion treatment for 15 to 30 minutes, and finally maintain mechanical stirring at 100 to 200 rpm, raise the water bath temperature to 50-60° C., maintain 50-60° C. and mechanical stirring at 100 to 200 rpm for 5 to 10 minutes, filter with filter paper, and send the obtained filter material to a vacuum drying oven and vacuum dry at 80 to 125° C. for 4 to 8 hours; Step three, the solid obtained in step two is placed in a planetary ball mill, and dry ball milled and dispersed at 60-80 rpm for 300-400 s to obtain a finished mixed filler, wherein the finished mixed filler consists of surface-modified silica powder, surface-modified inorganic fiber, and surface-modified glass microbeads.

[0019] By adopting the above technical scheme, it can be achieved that the inorganic fibers formed by surface-modified silicon micropowder, surface-modified inorganic fibers, and surface-modified glass microbeads can be dispersed more evenly in the phenolic resin curing system, effectively improving the filling density of the injection molded parts and eliminating the internal defects of the injection molded parts, thereby improving the dimensional stability, mechanical strength, aging resistance and impact toughness of the final product phenolic molding material, and better meeting the formability and operability requirements of the key components of the optical fiber fusion splicer.

[0020] In the second aspect, the present application provides a method for preparing a phenolic molding compound for key components of an optical fiber fusion splicer, which is achieved through the following technical solutions: A method for preparing a phenolic molding compound for key components of an optical fiber fusion splicer comprises the following steps: S1. Accurately weigh each component in the formula and mix it with a double-screw mixer for 8 to 10 minutes; S2. The material is conveyed to the feeder, and the material is fed to the co-rotating parallel twin-screw extruder through the feeder for mixing, and the material extruded by the extruder is pressed into a 1.5 to 2.0 mm thick sheet; S3. The slices are cooled and crushed to obtain phenolic molding compound powder for key components of optical fiber fusion splicing machines.

[0021] Preferably, the mixing parameters of the twin-screw extruder in S2 are as follows: the twin-screw extruder has a diameter of 75 mm, a length-to-diameter ratio of 20:1, the temperature of zone three is set to 50°C, the temperature of zone four is set to 80°C, the temperature of zone five is set to 80°C, the extruder speed is 180-185 rpm, and the feed rate of the feeder is 150±5 kg / min.

[0022] The preparation method of the present invention is relatively simple, has low operating difficulty, and meets the needs of industrial production.

[0023] In summary, this application has the following advantages: 1. Compared with the existing technology, the phenolic molding compound provided in the present invention has excellent heat resistance, low expansion coefficient, bending strength, good fluidity and low molding shrinkage, which can meet the requirements of good moldability and operability in the injection molding process of key components of optical fiber fusion splicers.

[0024] 2. The preparation method of the present invention is relatively simple, has low operating difficulty, and meets the needs of industrial production. DETAILED DESCRIPTION

[0025] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.

[0026] Embodiment: A phenolic molding compound for key components of an optical fiber fusion splicer is made of the following raw materials in parts by weight: 14 to 16 parts of a base-catalyzed nitrogen-containing phenolic resin, 25 to 35 parts of silicon powder, 20 to 25 parts of inorganic fibers, 25 to 35 parts of glass beads, 0.5 to 2 parts of a curing accelerator, 0.5 to 2 parts of a release agent, 0.5 to 2.5 parts of a coupling agent, 0.5 to 1.5 parts of a plasticizer, and 0.5 to 1.5 parts of a colorant.

[0027] The base-catalyzed nitrogen-containing phenolic resin is PF-8104 from Jinan Shengquan.

[0028] The average particle size of silicon powder is 100-200nm.

[0029] The inorganic fiber is at least one of alkali-free glass fiber, basalt fiber and inorganic whisker.

[0030] The monofilament diameter of the alkali-free glass fiber is preferably in the range of 9 to 11 μm.

[0031] The inorganic whisker is at least one of aluminum oxide whisker, aluminum nitride whisker, silicon dioxide whisker, silicon nitride whisker, polycrystalline mullite whisker, polycrystalline mullite ceramic whisker, and potassium titanate whisker.

[0032] Preferably, the inorganic fiber is composed of alkali-free glass fiber and inorganic whisker in a mass ratio of (9-19):1. Further preferably, the inorganic fiber is composed of alkali-free glass fiber, aluminum nitride whisker and silicon nitride whisker; the mass ratio of alkali-free glass fiber, aluminum nitride whisker and silicon nitride whisker is (40-45):(0.5-2.0):(0.5-1.0).

[0033] The glass beads were sieved through a 1800 mesh screen, with an average particle size of 5±0.2 μm. The particle size distribution curve of the glass beads shows D 10 =1.7~1.8μm, D 50 =4.8~5.2μm, D 90 =7.5~7.8μm.

[0034] Preferably, the glass beads are glass beads aggregate, which is composed of the following raw materials in percentage by mass: 5-10% of glass beads discharged from a 1250 mesh sieve, 50-75% of glass beads discharged from a 1800 mesh sieve, 10-30% of glass beads discharged from a 2500 mesh sieve, and the remainder of glass beads discharged from a 5000 mesh sieve.

[0035] Further preferably, the glass beads are glass beads aggregate, and the glass beads aggregate is composed of the following raw materials in the following mass percentages: 10% of glass beads discharged from a 1250 mesh sieve, 60% of glass beads discharged from a 1800 mesh sieve, 20% of glass beads discharged from a 2500 mesh sieve, and 10% of glass beads discharged from a 5000 mesh sieve.

[0036] The curing accelerator is calcium hydroxide and / or magnesium hydroxide.

[0037] Preferably, the curing accelerator is magnesium hydroxide or calcium hydroxide with a purity of >95% and a fineness of 2000 mesh.

[0038] The release agent is at least one of carnauba wax, polyethylene wax, stearic acid and stearate.

[0039] The coupling agent is at least one of mercaptosilane, epoxysilane and aminosilane.

[0040] The plasticizer is at least one of methanol, ethanol and polyethylene glycol.

[0041] Preferably, the plasticizer is polyethylene glycol PEG400.

[0042] The colorant is at least one of carbon black, oil-soluble aniline black, iron oxide brown, and iron oxide yellow.

[0043] It should be noted that the particle size of silicon micropowder, inorganic fiber and glass microbead is relatively small, and they are easy to agglomerate in the phenolic resin curing system, which in turn affects the dimensional stability and mechanical strength of the final product phenolic molding compound. Therefore, silicon micropowder, inorganic fiber and glass microbead must be surface modified before mixing.

[0044] The surface modification treatment method is as follows: Step 1: According to the ingredient list of phenolic molding compound for key parts of optical fiber fusion splicer, accurately measured silicon micropowder, inorganic fiber and glass microbeads are mixed evenly to obtain a mixed filler; at the same time, an aminosilane aqueous solution is prepared: 4 to 8 parts of aminosilane are mixed evenly with 992 to 996 parts of deionized water to obtain an aminosilane aqueous solution with a concentration of 0.4-0.8wt%; Step 2: add 5 to 10 parts of the mixed filler to 200 to 250 parts of the aminosilane aqueous solution, stir mechanically at 100 to 200 rpm for 5 to 10 minutes, then perform ultrasonic dispersion treatment for 15 to 30 minutes, and finally maintain mechanical stirring at 100 to 200 rpm, raise the water bath temperature to 50-60° C., maintain 50-60° C. and mechanical stirring at 100 to 200 rpm for 5 to 10 minutes, filter with filter paper, and send the obtained filter material to a vacuum drying oven and vacuum dry at 80 to 125° C. for 4 to 8 hours; Step three, the solid obtained in step two is placed in a planetary ball mill, and dry ball milled and dispersed at 60-80 rpm for 300-400 s to obtain a finished mixed filler, wherein the finished mixed filler consists of surface-modified silica powder, surface-modified inorganic fiber, and surface-modified glass microbeads.

[0045] A method for preparing a phenolic molding compound for key components of an optical fiber fusion splicer comprises the following steps: S1. Accurately weigh each component in the formula and mix it with a double-screw mixer for 8 to 10 minutes; S2. The material is conveyed to the feeder, and the material is fed to the co-rotating parallel twin-screw extruder through the feeder for mixing, and the material extruded by the extruder is pressed into a 1.5 to 2.0 mm thick sheet; Preferably, the mixing parameters of the twin-screw extruder in S2 are as follows: the diameter of the twin-screw extruder is 75 mm, the aspect ratio is 20:1, the temperature of the third zone is set to 50°C, the temperature of the fourth zone is set to 80°C, the temperature of the fifth zone is set to 80°C, the speed of the extruder is 180-185 rpm, and the feeding amount of the feeder is 150±5 kg / min; S3. The slices are cooled and crushed to obtain phenolic molding compound powder for key components of optical fiber fusion splicing machines.

[0046] Example 1: The ingredients of a phenolic molding compound for key components of an optical fiber fusion splicer are as follows: 150 parts by weight of PF-8104 alkali-catalyzed nitrogen-containing phenolic resin from Jinan Shengquan, 220 parts by weight of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, sourced from Hangzhou Gaoke Composite Materials Co., Ltd.), 280 parts by weight of glass microbeads (sourced from Shijiazhuang Wende Mineral Products Co., Ltd., 2500 mesh), 300 parts by weight of silicon micropowder (sourced from Suzhou Qiuyi New Materials Co., Ltd., made by ball milling 10000 mesh silicon micropowder in a planetary ball mill, medium particle size D 50 =150nm), 10 parts by mass of calcium hydroxide with a purity >95% and a fineness of 2000 mesh (customized by Xing'an Nanguo Jinlei Powder Factory), 10 parts by mass of release agent - Indonesian Sven Stearic Acid SA1801 (sourced from Guangdong Maotian Import and Export Co., Ltd.), 15 parts by mass of coupling agent aminosilane KH-550 (γ-aminopropyltriethoxysilane, sourced from Hangzhou Jessica Chemical Co., Ltd.), 5 parts by mass of plasticizer - polyethylene glycol PEG400 (sourced from Nantong Yongle Chemical Co., Ltd.), and 10 parts by mass of colorant - Cabot Carbon Black M900 (sourced from Guangzhou Shuojie New Materials Co., Ltd.).

[0047] A method for preparing a phenolic molding compound for key components of an optical fiber fusion splicer comprises the following steps: S1. Surface treatment of silica powder, inorganic fiber and glass beads; S1.1, place 2.2 parts by mass of alkali-free glass fiber chopped strands, 2.8 parts by mass of glass micro beads, and 3 parts by mass of silicon micro powder in a high-speed dispersing kettle and disperse at 600 rpm for 1 hour, and mix them evenly to obtain a mixed filler; At the same time, prepare an aminosilane KH-550 aqueous solution: 5 parts of aminosilane KH-550 and 995 parts of deionized water, stir magnetically at 200 rpm for 5 minutes, and mix well to obtain a 0.5 wt% aminosilane KH-550 aqueous solution; S1.2, add 8 parts of the mixed filler to 250 parts of the aminosilane aqueous solution, stir mechanically at 200 rpm for 8 min, then perform ultrasonic dispersion treatment for 30 min, ultrasonic frequency 40 kHz / power 600 W, finally maintain mechanical stirring at 200 rpm, heat the water bath to 55°C, maintain 55°C and 200 rpm mechanical stirring for 6 min, filter with filter paper, and send the obtained filter material to a vacuum drying oven and vacuum dry at 85°C for 5 h; S1.3, the solid obtained in S1.2 is placed in a planetary ball mill, and subjected to dry ball milling dispersion treatment at 80 rpm for 320 s to obtain a finished mixed filler, wherein the finished mixed filler consists of surface-modified silica powder, surface-modified inorganic fiber, and surface-modified glass microbeads; S2. Weigh 1.50 parts by weight of Jinan Shengquan's PF-8104 base-catalyzed nitrogen-containing phenolic resin, 8 parts by weight of the finished mixed filler in S1.3, 0.10 parts by weight of calcium hydroxide with a purity of >95% and a fineness of 2000 mesh, 0.10 parts by weight of a release agent - Indonesian Sven Stearic Acid SA1801, 0.15 parts by weight of a coupling agent aminosilane KH-550, 0.05 parts by weight of a plasticizer - polyethylene glycol PEG400, 0.10 parts by weight of a colorant - Cabot Carbon Black M900 and pour them into a formula tank, first mix with a glass rod for 1 minute, then input the materials in the formula tank into a double-screw ribbon mixer and mix them with a double-screw ribbon mixer for 10 minutes; S3. The material is conveyed to the feeder, and the material is fed to the co-rotating parallel twin-screw extruder through the feeder for mixing. The mixing parameters of the twin-screw extruder are as follows: the twin-screw extruder has a diameter of 75 mm, an aspect ratio of 20:1, the temperature of the third zone is set to 50 ° C, the temperature of the fourth zone is set to 80 ° C, the temperature of the fifth zone is set to 80 ° C, the extruder speed is 185 rpm, the feed rate of the feeder is 150 kg / min, and the material extruded by the extruder is pressed into a 1.5 mm thick sheet; S4. The thin slices obtained in S3 are cooled and crushed to obtain phenolic molding compound powder for key components of optical fiber fusion splicing machine.

[0048] The difference between Comparative Example 1 and Example 1 is that the ingredient list of a phenolic molding compound for key components of an optical fiber fusion splicer is as follows: 150 parts by mass of PF-8104 base-catalyzed nitrogen-containing phenolic resin from Jinan Shengquan, 440 parts by mass of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, sourced from Hangzhou Gaoke Composite Materials Co., Ltd.), 160 parts by mass of glass microbeads (sourced from Shijiazhuang Wende Mineral Products Co., Ltd., 2500 mesh), 200 parts by mass of silicon micropowder (sourced from Suzhou Qiuyi New Materials Co., Ltd., made by ball milling 10000 mesh silicon micropowder in a planetary ball mill, medium particle size D 50 =150nm), 10 parts by mass of calcium hydroxide with a purity >95% and a fineness of 2000 mesh (customized by Xing'an Nanguo Jinlei Powder Factory), 10 parts by mass of release agent - Indonesian Sven Stearic Acid SA1801 (sourced from Guangdong Maotian Import and Export Co., Ltd.), 15 parts by mass of coupling agent aminosilane KH-550 (γ-aminopropyltriethoxysilane, sourced from Hangzhou Jessica Chemical Co., Ltd.), 5 parts by mass of plasticizer - polyethylene glycol PEG400 (sourced from Nantong Yongle Chemical Co., Ltd.), and 10 parts by mass of colorant - Cabot Carbon Black M900 (sourced from Guangzhou Shuojie New Materials Co., Ltd.).

[0049] The difference between Comparative Example 2 and Example 1 is that the ingredient list of a phenolic molding compound for key components of an optical fiber fusion splicer is as follows: 300 parts by mass of linear phenolic resin (Allnex phenolic resin VPW 1946 46WA), 155 parts by mass of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, source Hangzhou Gaoke Composite Materials Co., Ltd.), 45 parts by mass of methenamine, 200 parts by mass of glass microbeads (source Shijiazhuang Wende Mineral Products Co., Ltd., 2500 mesh), 250 parts by mass of silicon micropowder (source Suzhou Qiuyi New Materials Co., Ltd., using 10000 mesh silicon micropowder as raw material and placed in a planetary ball mill to be ball milled, with a medium particle size D 50 =150nm), 10 parts by mass of calcium hydroxide with a purity>95% and a fineness of 2000 mesh (customized by Xing'an Nanguo Jinlei Powder Factory), 15 parts by mass of release agent - Indonesian Sven Stearic Acid SA1801 (sourced from Guangdong Maotian Import and Export Co., Ltd.), 10 parts by mass of coupling agent aminosilane KH-550 (γ-aminopropyltriethoxysilane, sourced from Hangzhou Jessica Chemical Co., Ltd.), and 10 parts by mass of colorant - Cabot Carbon Black M900 (Guangzhou Shuojie New Materials Co., Ltd.).

[0050] The difference between Comparative Example 3 and Example 1 is that the ingredient list of a phenolic molding compound for key components of an optical fiber fusion splicer is as follows: 300 parts by mass of PF-8104 base-catalyzed nitrogen-containing phenolic resin from Jinan Shengquan, 220 parts by mass of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, sourced from Hangzhou Gaoke Composite Materials Co., Ltd.), 210 parts by mass of glass microbeads (sourced from Shijiazhuang Wende Mineral Products Co., Ltd., 2500 mesh), 220 parts by mass of silicon micropowder (sourced from Suzhou Qiuyi New Materials Co., Ltd., made by ball milling 10000 mesh silicon micropowder in a planetary ball mill, medium particle size D 50 =150nm), 15 parts by mass of calcium hydroxide with a purity >95% and a fineness of 2000 mesh (customized by Xing'an Nanguo Jinlei Powder Factory), 15 parts by mass of release agent - Indonesian Sven Stearic Acid SA1801 (sourced from Guangdong Maotian Import and Export Co., Ltd.), 10 parts by mass of coupling agent aminosilane KH-550 (γ-aminopropyltriethoxysilane, sourced from Hangzhou Jessica Chemical Co., Ltd.), and 10 parts by mass of colorant - Cabot Carbon Black M900 (Guangzhou Shuojie New Materials Co., Ltd.).

[0051] 1. Bending Strength The bending strength of the phenolic molding materials injection molded in the examples and comparative examples was measured according to the test method in GB / T 9341-2008 “Determination of Flexural Properties of Plastics”.

[0052] 2. Heat resistance The heat deformation temperature of the phenolic molding materials injected in the examples and comparative examples was measured according to the test method in ISO 306 “Determination of Vicat softening temperature (VST) of plastic thermoplastic materials”.

[0053] 3. The glass transition temperature of the phenolic molding materials injected in the examples and comparative examples was determined by differential scanning calorimetry (DSC).

[0054] 4. Shrinkage determination method: Test the change rate of the material size of the phenolic molding plastics injected in the embodiments and comparative examples at the time of mold opening and the size after the mold, and determine the change rate of the material size of the phenolic molding plastics at the time of mold opening and the size after the mold on the X-axis, Y-axis, and Z-axis.

[0055] 5. Determination of thermal expansion coefficient: The thermal expansion coefficients of the phenolic molding materials injected in the examples and comparative examples were measured at -30°C and 30°C respectively using a fully automatic thermal expansion instrument in accordance with GB / T 1036-2008 "Determination of linear expansion coefficient of plastics at -30°C to 30°C - Quartz dilatometer method".

[0056] Data analysis Table 1: Test parameters of phenolic molding materials in Example 1 and Comparative Examples 1 to 3

[0057] Combining Example 1 and Comparative Examples 1 to 3 and Table 1, it can be seen that Example 1 shows very good consistency in thermal expansion coefficient and injection molding shrinkage in the three directions of X, Y, and Z relative to Comparative Examples 1, 2, and 3, and the dimensions of the parts are consistent, and the dimensional tolerance and position tolerance are relatively small. Downstream customers can realize the interchangeable assembly of optical lenses and micro-precision motors without subsequent repair and processing, solving the industry pain points. Therefore, the product of the present invention can be used for the injection molding production of key components of optical fiber fusion splicers.

[0058] In order to explore the effect of the particle size of silicon powder on the dimensional stability of the phenolic molding compound, the inventors measured the shrinkage rate and thermal expansion coefficient of the phenolic molding compounds in Examples 2-3 and Comparative Examples 4-5.

[0059] The difference between Example 2 and Example 1 is that the customized medium particle size D 50 =150nm silicon powder replaced by medium particle size D 50 =100nm silicon micropowder (customized by Suzhou Qiuyi New Materials Co., Ltd., using 10000 mesh silicon micropowder as raw material and ball milled in a planetary ball mill).

[0060] The difference between Example 3 and Example 1 is that the customized medium particle size D 50 =150nm silicon powder replaced by medium particle size D50 =200nm silicon micropowder (customized by Suzhou Qiuyi New Materials Co., Ltd., using 10000 mesh silicon micropowder as raw material and ball milled in a planetary ball mill).

[0061] The difference between Comparative Example 4 and Example 1 is that the customized medium particle size D 50 =150nm silicon powder replaced by medium particle size D 50 =500nm silicon micropowder (customized by Suzhou Qiuyi New Materials Co., Ltd., using 10000 mesh silicon micropowder as raw material and ball milled in a planetary ball mill).

[0062] The difference between Comparative Example 5 and Example 1 is that the customized medium particle size D 50 =150nm silicon powder replaced by medium particle size D 50 =2.6 μm 5000 mesh silica powder (customized by Suzhou Qiuyi New Materials Co., Ltd.).

[0063] Table 2: Test parameters of phenolic molding materials in Examples 1-3 and Comparative Examples 4-5

[0064] Combining Examples 1-3 and Comparative Examples 4-5 with Table 2, it can be seen that the median particle size D of the silicon powder is 50 =100-200nm, which can ensure that the silicon powder can be fully filled into the gaps between the resin and various fillers, increase the filling density of the injection molded parts to reduce the thermal expansion coefficient of the material, minimize the difference in shrinkage rates in all directions and improve the heat resistance of the material, while ensuring that the material has good fluidity and filling performance.

[0065] In the experiment, the medium particle size D 50 =150nm silicon powder replaces medium particle size D 50 =50nm silicon micropowder was used to extrude phenolic molding materials. It was found that there was obvious powder agglomeration on the surface of the thin slices produced by extrusion of phenolic molding materials. This shows that silicon micropowder with too fine particle size is prone to agglomeration and its compatibility with the phenolic resin matrix cannot be changed by simple surface treatment. It cannot meet the needs of industrial production, and the production cost of silicon micropowder with too fine particle size is also relatively high.

[0066] Based on silicon powder with medium particle size D 50 =150nm silicon powder, the technical schemes of Examples 4-6 were tested to explore the influence of inorganic fiber composition on the dimensional stability and mechanical strength of the prepared phenolic molding compound.

[0067] The difference between Example 4 and Example 1 is that 220 parts by mass of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, source Hangzhou Hi-Tech Composite Materials Co., Ltd.) are replaced by 208 parts by mass of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, source Hangzhou Hi-Tech Composite Materials Co., Ltd.) and 12 parts by mass of aluminum nitride whiskers (diameter 0.2-0.6 μm, length 50-100 μm, provided by Angxing New Carbon Materials Changzhou Co., Ltd.).

[0068] The difference between Example 5 and Example 1 is that 220 parts by mass of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, source Hangzhou Hi-Tech Composite Materials Co., Ltd.) are replaced by 200 parts by mass of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, source Hangzhou Hi-Tech Composite Materials Co., Ltd.) and 20 parts by mass of aluminum nitride whiskers (diameter 0.2-0.6 μm, length 50-100 μm, provided by Angxing New Carbon Materials Changzhou Co., Ltd.).

[0069] The difference between Example 6 and Example 1 is that 220 parts by mass of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, source Hangzhou Gaoke Composite Materials Co., Ltd.) are replaced by 205 parts by mass of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, source Hangzhou Gaoke Composite Materials Co., Ltd.), 10 parts by mass of aluminum nitride whiskers (diameter 0.2-0.6 μm, length 50-100 μm, provided by Angxing New Carbon Materials Changzhou Co., Ltd.) and 5 parts by mass of silicon nitride whiskers (content 98wt%, diameter 0.2-1.0 μm, length 5-10 μm, specific surface area 15m 2 / g, grade A, provided by Wuhan Kemik Biopharmaceutical Technology Co., Ltd.).

[0070] Table 3: Test parameters of phenolic molding materials in Example 1 and Examples 4-6

[0071] It can be seen from Example 1 and Examples 4-6 and Table 3 that the phenolic molding compound prepared from the inorganic fiber formed by the combination of the alkali-free glass fiber and the inorganic whisker has relatively good dimensional stability and mechanical strength. Preferably, aluminum nitride whiskers and silicon nitride whiskers are compounded as the inorganic whiskers, and the inorganic whiskers and the alkali-free glass fiber are compounded in a mass ratio of 41:2:1 to form the inorganic fiber.

[0072] Based on silicon powder with medium particle size D 50=150nm silicon micropowder and 220 parts by mass of alkali-free glass fiber chopped strands in the formula are replaced by 205 parts by mass of alkali-free glass fiber chopped strands, 10 parts by mass of aluminum nitride whiskers and 5 parts by mass of silicon nitride whiskers, the technical schemes of Test Examples 7-9 and Comparative Example 6 are tested to explore the influence of the particle size of glass microbeads on the dimensional stability and mechanical strength of the prepared phenolic molding compound.

[0073] The difference between Example 7 and Example 1 is that the ingredient list of a phenolic molding compound for key components of an optical fiber fusion splicer is as follows: 150 parts by mass of Jinan Shengquan's PF-8104 base-catalyzed nitrogen-containing phenolic resin, 205 parts by mass of alkali-free glass fiber chopped strands (customized length 3 mm, diameter 9-11 μm, source Hangzhou Gaoke Composite Materials Co., Ltd.), 10 parts by mass of aluminum nitride whiskers (diameter 0.2-0.6 μm, length 50-100 μm, provided by Angxing New Carbon Materials Changzhou Co., Ltd.) and 5 parts by mass of silicon nitride whiskers (content 98wt%, diameter 0.2-1.0 μm, length 5-10 μm, specific surface area 15m 2 / g, Grade A, provided by Wuhan Kemik Biopharmaceutical Technology Co., Ltd.), 280 parts by mass of 1800 mesh sieved glass microbeads (source: Shijiazhuang Wende Mineral Products Co., Ltd., D 10 =1.8μm, D 50 =5.0μm, D 90 =7.7μm), 300 parts by mass of silicon micropowder (from Suzhou Qiuyi New Materials Co., Ltd., made by ball milling 10000 mesh silicon micropowder in a planetary ball mill, with a medium particle size D 50 =150nm), 10 parts by mass of calcium hydroxide with a purity>95% and a fineness of 2000 mesh (customized by Xing'an Nanguo Jinlei Powder Factory), 10 parts by mass of release agent - Indonesian Sven Stearic Acid SA1801 (sourced from Guangdong Maotian Import and Export Co., Ltd.), 15 parts by mass of coupling agent aminosilane KH-550 (γ-aminopropyltriethoxysilane, sourced from Hangzhou Jessica Chemical Co., Ltd.), 5 parts by mass of plasticizer - polyethylene glycol PEG400 (sourced from Nantong Yongle Chemical Co., Ltd.), and 10 parts by mass of colorant - Cabot Carbon Black M900 (Guangzhou Shuojie New Materials Co., Ltd.).

[0074] The difference between Example 8 and Example 7 is that 280 parts by mass of 1800 mesh glass microspheres (source: Shijiazhuang Wende Mineral Products Co., Ltd.) in the phenolic molding compound formula are replaced by 168 parts by mass of 1800 mesh glass microspheres (source: Shijiazhuang Wende Mineral Products Co., Ltd.) and 112 parts by mass of 2500 mesh glass microspheres (source: Shijiazhuang Wende Mineral Products Co., Ltd.).

[0075] The difference between Example 9 and Example 7 is that 280 parts by mass of 1800 mesh glass beads (source: Shijiazhuang Wende Mineral Products Co., Ltd.) in the phenolic molding compound formula are replaced by 28 parts by mass of 1250 mesh glass beads (source: Shijiazhuang Wende Mineral Products Co., Ltd.), 168 parts by mass of 1800 mesh glass beads (source: Shijiazhuang Wende Mineral Products Co., Ltd.), 56 parts by mass of 2500 mesh glass beads, and 28 parts by mass of 5000 mesh glass beads.

[0076] The difference between Comparative Example 6 and Example 7 is that 280 parts by mass of 1800-mesh glass microspheres (source: Shijiazhuang Wende Mineral Products Co., Ltd.) in the phenolic molding compound formula are replaced by 280 parts by mass of 1000-mesh glass microspheres (source: Shijiazhuang Wende Mineral Products Co., Ltd.).

[0077] Table 4: Test parameters of phenolic molding materials in Examples 6-9 and Comparative Example 6

[0078] Combining Examples 6-9 with Example 6 and Table 4, it can be seen that the glass bead aggregate formed by 10% of glass beads discharged from a 1250 mesh sieve, 60% of glass beads discharged from a 1800 mesh sieve, 20% of glass beads discharged from a 2500 mesh sieve, and 10% of glass beads discharged from a 5000 mesh sieve has the best comprehensive performance in terms of dimensional stability and mechanical strength of the phenolic molding material. The reason is that the glass bead aggregate can be more fully filled into the gaps between the resin and various fillers, and the defective voids inside the phenolic molding material can be largely eliminated.

[0079] Based on the phenolic molding compound formula provided in Example 1, the technical solution of Comparative Example 7 was tested to explore the influence of the phenolic molding compound preparation process on the dimensional stability and mechanical strength of the prepared phenolic molding compound.

[0080] The difference between Comparative Example 7 and Example 1 is that: a method for preparing a phenolic molding compound for key components of an optical fiber fusion splicer comprises the following steps: S1. 2.2 parts by mass of alkali-free glass fiber chopped strands, 2.8 parts by mass of glass beads, and 3 parts by mass of silicon powder were placed in a high-speed dispersion kettle at 600 rpm for 1h and mixed to obtain a mixed filler; S2. Weigh 1.50 parts by mass of Jinan Shengquan PF-8104 base-catalyzed nitrogen-containing phenolic resin, 8 parts by weight of the mixed filler in S1, 0.10 parts by mass of calcium hydroxide with a purity of> 95% and a fineness of 2000 mesh, 0.10 parts by mass of a release agent - Indonesian Sven stearic acid SA1801, 0.15 parts by mass of a coupling agent aminosilane KH-550, 0.05 parts by mass of a plasticizer - polyethylene glycol PEG400, 0.10 parts by mass of a colorant - Cabot carbon black M900, and pour them into the formula tank. After mixing with a glass rod for 1 minute, the materials in the formula tank are input into a double-screw mixer and mixed with a double-screw mixer for 10 minutes; S3. The material discharged from the twin-screw mixer is conveyed to a feeder, and then fed to a co-rotating parallel twin-screw extruder through the feeder for mixing. The mixing parameters of the twin-screw extruder are as follows: the diameter of the twin-screw extruder is 75 mm, the aspect ratio is 20:1, the temperature of the third zone is set to 50°C, the temperature of the fourth zone is set to 80°C, the temperature of the fifth zone is set to 80°C, the extruder speed is 185 rpm, the feed rate of the feeder is 150 kg / min, and the material extruded by the extruder is pressed into a 1.5 mm thick sheet; S4. The thin slices obtained in S3 are cooled and crushed to obtain phenolic molding compound powder for key components of optical fiber fusion splicing machine.

[0081] Table 5: Test parameters of phenolic molding materials in Example 1 and Comparative Example 7

[0082] From Example 1 and Comparative Example 7 and Table 5, it can be seen that the microsilica powder, inorganic fibers and glass microbeads must be surface-modified before compounding so that the surface-modified microsilica powder, inorganic fibers and glass microbeads can be more evenly dispersed in the phenolic resin matrix, thereby improving the density, dimensional stability and mechanical strength of the phenolic molding compound. That is, the microsilica powder, inorganic fibers and glass microbeads must be surface-treated.

[0083] In summary, the phenolic molding compound provided in the present invention has the advantages of relatively consistent thermal expansion coefficients in all directions (X, Y, Z), and a low shrinkage rate. The shrinkage rates in all directions (X, Y, Z) are relatively consistent and stable, which meets the requirements of good formability and operability during the injection molding of key components of optical fiber fusion splicers. In addition, the phenolic molding compound for key components of optical fiber fusion splicers provided in the present invention has a higher temperature resistance grade, HDT ≥ 300°C, which meets the requirements of heat-resistant processing during the injection molding of key components of optical fiber fusion splicers, and has excellent resistance to thermal oxidation degradation.

[0084] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A phenolic molding compound for key components of an optical fiber fusion splicer, characterized in that: The invention is prepared from the following raw materials in parts by weight: 14 to 16 parts of base-catalyzed nitrogen-containing phenolic resin, 25 to 35 parts of silicon powder, 20 to 25 parts of inorganic fiber, 25 to 35 parts of glass microspheres, 0.5 to 2 parts of curing accelerator, 0.5 to 2 parts of release agent, 0.5 to 2.5 parts of coupling agent, 0.5 to 1.5 parts of plasticizer, and 0.5 to 1.5 parts of colorant; The average particle size of the silicon powder is 100 to 200 nm; The inorganic fiber is at least one of alkali-free glass fiber, basalt fiber, and inorganic whisker; The curing accelerator is calcium hydroxide and / or magnesium hydroxide; The release agent is at least one of carnauba wax, polyethylene wax, stearic acid, and stearate; The coupling agent is at least one of mercaptosilane, epoxysilane and aminosilane; The plasticizer is at least one of methanol, ethanol and polyethylene glycol; The colorant is at least one of carbon black, oil-soluble aniline black, iron oxide brown, and iron oxide yellow.

2. The phenolic molding compound for key components of an optical fiber fusion splicer according to claim 1, characterized in that: The base-catalyzed nitrogen-containing phenolic resin is PF-8104 from Jinan Shengquan.

3. The phenolic molding compound for key components of an optical fiber fusion splicer according to claim 1, characterized in that: The inorganic whisker is at least one of aluminum oxide whisker, aluminum nitride whisker, silicon dioxide whisker, silicon nitride whisker, polycrystalline mullite whisker, polycrystalline mullite ceramic whisker, and potassium titanate whisker.

4. The phenolic molding compound for key components of an optical fiber fusion splicer according to claim 1, characterized in that: The inorganic fiber is composed of alkali-free glass fiber and inorganic whisker in a mass ratio of (9-19):

1.

5. The phenolic molding compound for key components of an optical fiber fusion splicer according to claim 4, characterized in that: The inorganic fiber is composed of alkali-free glass fiber, aluminum nitride whisker and silicon nitride whisker; the mass ratio of the alkali-free glass fiber, aluminum nitride whisker and silicon nitride whisker is (40-45):(0.5-2.0):(0.5-1.0).

6. The phenolic molding compound for key components of an optical fiber fusion splicer according to claim 1, characterized in that: The glass microspheres are 1800 mesh sieve out materials, the average particle size is 5±0.2 μm; the particle size distribution curve of the glass microspheres shows D 10 =1.7~1.8μm, D 50 =4.8~5.2μm, D 90 =7.5~7.8μm.

7. The phenolic molding compound for key components of an optical fiber fusion splicer according to claim 1, characterized in that: The glass beads are glass beads aggregate, which is composed of the following raw materials in percentage by mass: 5-10% of glass beads discharged from a 1250 mesh sieve, 50-75% of glass beads discharged from a 1800 mesh sieve, 10-30% of glass beads discharged from a 2500 mesh sieve, and the remainder of glass beads discharged from a 5000 mesh sieve.

8. The phenolic molding compound for key components of an optical fiber fusion splicer according to claim 1, characterized in that: The silicon micropowder, inorganic fiber and glass microbeads all need to be surface modified before mixing. The surface modification treatment method is as follows: Step 1: According to the ingredient list of phenolic molding compound for key parts of optical fiber fusion splicer, accurately measured silicon micropowder, inorganic fiber and glass microbeads are mixed evenly to obtain a mixed filler; at the same time, an aminosilane aqueous solution is prepared: 4 to 8 parts of aminosilane are mixed evenly with 992 to 996 parts of deionized water to obtain an aminosilane aqueous solution with a concentration of 0.4-0.8wt%; Step 2: add 5 to 10 parts of the mixed filler to 200 to 250 parts of the aminosilane aqueous solution, stir mechanically at 100 to 200 rpm for 5 to 10 minutes, then perform ultrasonic dispersion treatment for 15 to 30 minutes, and finally maintain mechanical stirring at 100 to 200 rpm, raise the water bath temperature to 50-60° C., maintain 50-60° C. and mechanical stirring at 100 to 200 rpm for 5 to 10 minutes, filter with filter paper, and send the obtained filter material to a vacuum drying oven and vacuum dry at 80 to 125° C. for 4 to 8 hours; Step three, the solid obtained in step two is placed in a planetary ball mill, and dry ball milled and dispersed at 60-80 rpm for 300-400 s to obtain a finished mixed filler, wherein the finished mixed filler consists of surface-modified silica powder, surface-modified inorganic fiber, and surface-modified glass microbeads.

9. A method for preparing a phenolic molding compound for key components of an optical fiber fusion splicer according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Accurately weigh each component in the formula and mix it with a double-screw mixer for 8 to 10 minutes; S2. The material is conveyed to the feeder, and the material is fed to the co-rotating parallel twin-screw extruder through the feeder for mixing, and the material extruded by the extruder is pressed into a 1.5 to 2.0 mm thick sheet; S3. The slices are cooled and crushed to obtain phenolic molding compound powder for key components of optical fiber fusion splicing machines.

10. The method for preparing a phenolic molding compound for key components of an optical fiber fusion splicer according to claim 9, characterized in that: The mixing parameters of the twin-screw extruder in S2 are as follows: twin-screw extruder diameter 75 mm, aspect ratio 20:1, zone three temperature set to 50°C, zone four temperature set to 80°C, zone five temperature set to 80°C, extruder speed 180-185 rpm, feeder feeding amount 150±5 kg / min.

Citation Information

Patent Citations

  • Carbon fiber reinforced injected phenolic moulding plastic and preparation method thereof

    CN103923434A

  • Preparation method of high-thermal-conductivity graphene phenolic moulding plastic

    CN115746498A

  • Phenolic resin molding material and molding

    JP2015224309A